2019
DOI: 10.1088/1755-1315/393/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic and inorganic fertilizer applications on N, P-uptake, K-uptake and yield of sweet corn (Zea mays saccharata Sturt)

Abstract: This study was conducted to evaluate the effect of organic fertilizer (i.e. cow manure) and inorganic fertilizer application on nutrient uptake and yield of sweet corn (Zea mays saccharata Sturt). Inceptisols possesses low soil fertility and relatively low to moderate level of organic matter content. Application of organic fertilizer in combination with inorganic fertilizers is expected to increase N, P and K uptake and yield of sweet corn. This study has been conducted from October 2018 to February 2019 at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 4 publications
2
24
0
3
Order By: Relevance
“…Research from [44] also resulted that applying K at 120 kg ha -1 increased tuber yields by about 47% compared to control treatment (12.96 tonnes ha -1 ). Likewise, the results of research by [70] showed that the yield of sweet corn crops, [71] rice, [72] Portulaca oleracea L, increased due to a combination of organic fertilizer with NPK fertilizer compared to control treatment. The recommended dosage from the research is three-quarter NPK and half of organic fertilizer.…”
Section: Biomass Of Growth and Yield Components Of Clover Plants At Various Doses Of Organic And Inorganic Fertilizersmentioning
confidence: 99%
“…Research from [44] also resulted that applying K at 120 kg ha -1 increased tuber yields by about 47% compared to control treatment (12.96 tonnes ha -1 ). Likewise, the results of research by [70] showed that the yield of sweet corn crops, [71] rice, [72] Portulaca oleracea L, increased due to a combination of organic fertilizer with NPK fertilizer compared to control treatment. The recommended dosage from the research is three-quarter NPK and half of organic fertilizer.…”
Section: Biomass Of Growth and Yield Components Of Clover Plants At Various Doses Of Organic And Inorganic Fertilizersmentioning
confidence: 99%
“…These were followed by NPKtreated plants with mean heights of 62cm in 2018 and 54 cm in 2019. The higher plant height due to DAP and NPK application compared to FYM and control is associated with the fact that nutrients in inorganic fertilizer are readily available for plant uptake while FYM releases nutrients slowly [10,11]. Control plots had the shortest plants due to poor soil fertility.…”
Section: Plant Heightmentioning
confidence: 99%
“…Nitrogen fertilization increases maize grain yield (43-68%) and biomass (25-42%). Organic and inorganic nitrogen sources have a positive interaction for increasing crop yield and improving soil fertility (Mahmood et al, 2017;Mamiev et al, 2019;Partey et al, 2018;Sofyan et al, 2019;Tonitto & Ricker-Gilbert, 2016). Synergistic effects of nitrogen and organic manure accumulate more total nitrogen in the soil.…”
Section: Introductionmentioning
confidence: 99%